OCTA ischemic changes in three patients with unexplained severe visual loss related to silicone oil tamponade - Piotr Lasota (Klinika Oczna)
Our report describes a series of three patients with irreversible visual loss after use of silicone oil tamponade. They were operated on by vitrectomy with silicone oil injection due to rhegmatogenous retinal detachment. Postoperatively, optical coherence tomography angiography showed an increase of the foveal avascular zone of the deep retinal plexus and a decrease in density of foveal capillaries. These findings may suggest foveal ischemia as a cause of unexplained visual loss.